COMPLEX DYNAMICS: ANALYZING THE PROFOUND IMPACT OF RELIGIOUS EDUCATION DEPTH ON INTERFAITH TOLERANCE LEVELS IN A MULTICULTURAL SOCIETY IN THE GLOBALIZATION ERA - Ani Nafisah; Muhammad Muttaqin; Doby Indrawan; Zainuddin; Jajang Rustandi (Adisam Publisher, 2023)
This study delved into the complex dynamics surrounding the profound impact of religious education depth on interfaith tolerance levels within a multicultural society during globalization. Employing a mixed-methods research design, the investigation sought to provide a nuanced understanding by integrating qualitative and quantitative approaches. The research was grounded in a comprehensive literature review, identifying gaps and establishing the theoretical foundation for the study. The study aimed to ensure diverse perspectives by utilizing a stratified random sampling technique based on religious affiliation, educational background, and geographic location. Qualitative data collection involved in-depth interviews and focus group discussions, exploring participants' experiences and perceptions regarding the influence of religious education on interfaith tolerance. Concurrently, a quantitative phase utilized structured surveys with standardized scales to measure religious education depth, interfaith tolerance levels, and relevant demographics. Thematic analysis was applied to qualitative data, extracting patterns and themes, while quantitative data underwent statistical analysis, including descriptive statistics and correlation and regression analyses. Ethical considerations were paramount throughout the study, with participants providing informed consent and strict confidentiality measures in place. Triangulation of methods enhanced the validity and reliability of the study, contributing to a robust exploration of the intricate relationship between religious education and interfaith tolerance. This research offered valuable insights applicable to educational policies, societal initiatives, and global conversations on fostering peaceful coexistence amid religious diversity.